A Case Report: Thoracotomy in 64 years old Women with Thoracic Empyema - Nugroho Sofian Aji; Darmawan Ismail (International Medical Journal Corp. Ltd, 2025)
Background. Thoracic empyema, a serious complication of pneumonia, often begins with conservative treatments like thoracentesis and antibiotics in its early stages. However, the management of advanced empyema, particularly in stage II and III, remains contentious. Traditionally, open thoracotomy and decortication have been viewed as requiring lengthy recovery and extended hospital stays, leading some to favor thoracoscopic approaches for quicker outcomes. Objective. This study reports on the management of thoracotomy in patients with thoracic empyema. Case Report. A 64-year-old woman had been experiencing a cough with blood-streaked sputum for the past 2 months, which did not improve with medication. Further examination indicated thoracic empyema. An open thoracotomy was performed to manage the thoracic empyema. Conclusion. Open thoracotomy proves to be a beneficial approach for managing thoracic empyema. The procedure facilitates effective drainage and resolution of the infection, leading to improved recovery outcomes.